2007
DOI: 10.1063/1.2815730
|View full text |Cite
|
Sign up to set email alerts
|

Achieving large slip with superhydrophobic surfaces: Scaling laws for generic geometries

Abstract: We investigate the hydrodynamic friction properties of superhydrophobic surfaces and quantify their superlubricating potential. On such surfaces, the contact of the liquid with the solid roughness is minimal, while most of the interface is a liquid-gas one, resulting in strongly reduced friction. We obtain scaling laws for the effective slip length at the surface in terms of the generic surface characteristics ͑roughness length scale, depth, solid fraction of the interface, etc.͒. These predictions are success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
501
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(556 citation statements)
references
References 34 publications
46
501
4
1
Order By: Relevance
“…Analytical models and numerical simulations are useful tools in understanding slip lengths in laminar flows on a few simple surface patterns such as grates (ridges, trenches) (Philip 1972a, b;Lauga and Stone 2003;Belyaev and Vinogradova 2010a;Asmolov and Vinogradova 2012), posts (pillars) (Ybert et al 2007;Davis and Lauga 2010), and holes (Ybert et al 2007;Davis and Lauga 2009a), as shown in Fig. 2.…”
Section: Liquid Slips On Shpo Surfaces: Theoretical Predictionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analytical models and numerical simulations are useful tools in understanding slip lengths in laminar flows on a few simple surface patterns such as grates (ridges, trenches) (Philip 1972a, b;Lauga and Stone 2003;Belyaev and Vinogradova 2010a;Asmolov and Vinogradova 2012), posts (pillars) (Ybert et al 2007;Davis and Lauga 2010), and holes (Ybert et al 2007;Davis and Lauga 2009a), as shown in Fig. 2.…”
Section: Liquid Slips On Shpo Surfaces: Theoretical Predictionsmentioning
confidence: 99%
“…Analytical solutions for slip lengths on posts were derived for large gas fractions (i.e., φ g > 0.3) as follows (Davis and Lauga 2010): In case of holes, a logarithmic dependency of slip length on gas fraction was derived analytically (Ybert et al 2007): where A and B are prefactors obtained by numerical simulations. For an example, in the case of circular holes at a gas fraction between 0.25 and 0.78, they were obtained as A = 0.134 and B = −0.023 (Ng and Wang 2010).…”
Section: Influence Of Structural Parameters On Slip Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent theoretical predictions and experimental results have pointed to the possibility to create huge (more than 10 mm) slip lengths by the use of composite surfaces (Choi & Kim 2006;Ybert et al 2007). mPIV is a particularly appropriate method to measure the slippage on such surfaces, thanks to its ability to precisely reconstruct the speed profile with a submicrometre resolution, as has already been demonstrated on carbon nanotube-coated surfaces (Joseph et al 2006).…”
Section: Micro-and Nanovelocimetrymentioning
confidence: 99%